Researchers made their marks at INPEX, US - UMP, PNC
Universiti Malaysia Pahang (UMP) made its mark at the international scene when four gold medals were won in the Invention and New Product Exposition (INPEX 2012) held at Monroeville Convention Center, in Pittsburgh, US, on June 15, 2012.